Adapting Dialectical Behavior Therapy for Acute-Care Inpatient Adolescents. Issue 4 (2nd October 2022) - Tebbett-Mock, Alison A.; McGee, Madeline; Saito, Ema
ABSTRACT: This article describes the adaptation of Dialectical Behavior Therapy (DBT) for an acute-care psychiatric inpatient unit for adolescents with a range of diagnoses. There is a growing body of research demonstrating the efficacy of DBT for inpatient adolescents with a range of psychiatric diagnoses. Although the application of DBT has been described for adult inpatient settings, program descriptions and recommendations for adolescents differ from adults and are lacking for an acute-care inpatient adolescent setting. Further, clinical recommendations of DBT applied to adult inpatient settings, as well as adolescent outpatient settings, have largely focused on treatment for those with borderline personality disorder and/or symptoms, rather than a range of psychiatric diagnoses. Given the demonstrated efficacy of our DBT program for adolescents presenting with a range of psychiatric diagnoses, (Saito et al., 2020 ; Tebbett-Mock et al., 2020 ), this manuscript aims to address the need for a clinical resource on adapting DBT for acute-care inpatient adolescents. Informed by an implementation framework, we outline phases of our process for adapting DBT to an acute-care adolescent inpatient setting including 1) describing our institution, team, and patient population, 2) selection of DBT as a treatment model, 3) establishing and maintaining stakeholder engagement and partnerships, 4) DBT training, 5) developing and implementing DBT treatment modes and functions, 6) program evaluation and dissemination, and 7) identifying practice considerations, limitations, and future directions.